Hours of Work and Gender Identity: Does Part-Time Work Make the Family Happier? - Van Ours, J; Booth, A (My University, 2005)
Taking into account inter-dependence within the family, we investigate the relationship between part-time work and happiness. We use panel data from the new Household, Income and Labor Dynamics in Australia Survey. Our analysis indicates that part-time women are more satisfied with working hours than full-time women. Partnered women’s life satisfaction is increased if their partners work full-time. Male partners’ life satisfaction is unaffected by their partners’ market hours but is increased if they themselves are working full-time. This finding is consistent with the gender identity hypothesis of Akerlof and Kranton (2000).
IZA Discussion Paper Series
Keywords: Employment; Employment -- Hours; Satisfaction; Labour market; Employment and unemployment